Rheology of Industrial Polysaccharides: Theory and Applications 1995
DOI: 10.1007/978-1-4615-2185-3_4
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of polysaccharide systems

Abstract: The transport properties and, specifically, the rheological behavior of real and complex materials such as polysaccharide systems can be significantly affected by several factors, mainly related to molecular and supermolecular features. Most of these factors are common to all polymeric systems, as they have universal character; others are peculiar to carbohydrate polymers. If we bear in mind the concepts discussed in §1.4, we can easily imagine for polysaccharides a variety of structural conditions much wider … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 581 publications
(501 reference statements)
3
35
0
1
Order By: Relevance
“…In this study, the slope value of LBG alone was greater than unity. In dilute regimes, slope values greater than unity have been reported to be associated with random coil conformation (Lapasin & Pricl, 1995) or entanglement (Morris et al, 1981). In dilute regimes, slope values less than 1 have been reported to be associated with rod-like conformation (Lai & Chiang, 2002).…”
Section: Molecular Conformation and Polymer Interactionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the slope value of LBG alone was greater than unity. In dilute regimes, slope values greater than unity have been reported to be associated with random coil conformation (Lapasin & Pricl, 1995) or entanglement (Morris et al, 1981). In dilute regimes, slope values less than 1 have been reported to be associated with rod-like conformation (Lai & Chiang, 2002).…”
Section: Molecular Conformation and Polymer Interactionmentioning
confidence: 96%
“…The data did not fit with the linear regression model. Lapasin and Pricl (1995) reported that neutral polysaccharides (i.e., LBG) exhibited linear plots of lower slope, whereas ionic polysaccharides (i.e., xanthan) displayed a sharp increase of the slope, possibly due to expanded coil dimensions and electrostatic repulsion between chain segments. Pals and Hermans (1952) reported that g sp C increased rapidly at greater dilutions in sodium pectate without salts.…”
Section: Intrinsic Viscositymentioning
confidence: 97%
“…The geometry used for the tests was a cross-hatch plate device (Haake PP35 TI: diameter = 35 mm), in order to reduce the extent of the wall slippage phenomena [22].…”
Section: Rheological Characterizationmentioning
confidence: 99%
“…where the υ constant used for this study equal 1.3 (Lapasin, R., et al, 1995). Table 1 shows the solubility of Gum Habeil increased with the solvent basicity directly, the high solubility of gum solution in sodium carbonate due to calcium ion depletion.…”
Section: Salt Tolerance and Chain Stiffness Parametermentioning
confidence: 99%
“…Standard methods were used to prepare soluble part, and deacetylated gum solutions (Le Cerf, D., et al, 1990, Lapasin, R., & Pricl, S., 1995.…”
Section: Preparation Of Deacetylated and Soluble Part Gum Solutionsmentioning
confidence: 99%